2014
DOI: 10.1038/labinvest.2014.122
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts induce expression of FGF4 in ovarian cancer stem-like cells/cancer-initiating cells and upregulate their tumor initiation capacity

Abstract: Cancer stem-like cells (CSCs)/cancer-initiating cells (CICs) are defined as a small population of cells within cancer that contribute to cancer initiation and progression. Cancer-associated fibroblasts (CAFs) are stromal fibroblasts surrounding tumor cells, and they have important roles in tumor growth and tumor progression. It has been suggested that stromal fibroblasts and CSCs/CICs might mutually cooperate to enhance their growth and tumorigenic capacity. In this study, we investigated the effects of fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…They then activate downstream signal molecules during epithelial-to-mesenchymal transition of tumor cells (40). Some researchers suggested that the expression of FGF4 and FGFR2 in ovarian cancer stemlike cells/cancer-initiating cells promoted their tumor initiation capacity (41). Our mass spectrometry results show that PIWIL4 promotes the TGF-␤ and FGF signaling pathways in the breast cancer cell line MDA-MB-231, which links PIWIL4 function to these important signaling pathways.…”
Section: Discussionsupporting
confidence: 52%
“…They then activate downstream signal molecules during epithelial-to-mesenchymal transition of tumor cells (40). Some researchers suggested that the expression of FGF4 and FGFR2 in ovarian cancer stemlike cells/cancer-initiating cells promoted their tumor initiation capacity (41). Our mass spectrometry results show that PIWIL4 promotes the TGF-␤ and FGF signaling pathways in the breast cancer cell line MDA-MB-231, which links PIWIL4 function to these important signaling pathways.…”
Section: Discussionsupporting
confidence: 52%
“…Conversely, co-overexpression of Zeb1 and Zeb2 enhanced sphere-forming ability of head and neck cancer cells [57]. FGF4 is shown to play a key role in maintaining self-renewal capacity of normal and cancer stem cells [58, 59]. FGF4 promoted self-renewal of CSC-enriched population [59].…”
Section: Discussionmentioning
confidence: 99%
“…FGF4 is shown to play a key role in maintaining self-renewal capacity of normal and cancer stem cells [58, 59]. FGF4 promoted self-renewal of CSC-enriched population [59]. …”
Section: Discussionmentioning
confidence: 99%
“…The stroma has also been shown to promote the acquisition of stem-like properties by cancer cells, providing a fertile niche in which primary cancer cells can grow, and metastatic cancer cells can colonize 183,184 . The early stages of colon cancer are thought to be driven by the stem cell niche: stromal fibroblasts secrete Wnt ligands that promote β-catenin-dependent signalling in colon epithelial cells, driving a cancer stem cell-like phenotype 185 .…”
Section: Stroma–cancer Interactionsmentioning
confidence: 99%